2014
DOI: 10.1162/jocn_a_00619
|View full text |Cite
|
Sign up to set email alerts
|

Conscious and Unconscious Representations of Observed Actions in the Human Motor System

Abstract: Action observation activates the observer's motor system. These motor resonance responses are automatic and triggered even when the action is only implied in static snapshots. However, it is largely unknown whether an action needs to be consciously perceived to trigger motor resonance. In this study, we used single-pulse TMS to study the facilitation of corticospinal excitability (a measure of motor resonance) during supraliminal and subliminal presentations of implied action images. We used a forward and back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 71 publications
2
14
0
Order By: Relevance
“…For example, Gangitano et al (2004) reported suppression of mirror-like facilitation when participants saw an unnatural grasping obtained by delaying finger aperture. A similar suppression effect was obtained by Tomeo et al (2013) when expert goalkeepers observed kicking actions containing incongruent body kinematics and by Mattiassi et al (2014) when the observers viewed a sequence of 2 incongruent finger movements, even if the first movement was masked not to be consciously detected by the participants. In a similar vein, when the observers expected a specific kinematic pattern depending on a semantic cue informing on the object weight (Senot et al 2011) or affordance (Janssen et al 2015) or on the context of the action (Amoruso and Urgesi 2016), observation of an action pattern that disconfirmed their expectations suppressed motor resonance.…”
Section: The Muscle-specific Cse Decrease Mirrors Kinematic Adaptationssupporting
confidence: 60%
See 1 more Smart Citation
“…For example, Gangitano et al (2004) reported suppression of mirror-like facilitation when participants saw an unnatural grasping obtained by delaying finger aperture. A similar suppression effect was obtained by Tomeo et al (2013) when expert goalkeepers observed kicking actions containing incongruent body kinematics and by Mattiassi et al (2014) when the observers viewed a sequence of 2 incongruent finger movements, even if the first movement was masked not to be consciously detected by the participants. In a similar vein, when the observers expected a specific kinematic pattern depending on a semantic cue informing on the object weight (Senot et al 2011) or affordance (Janssen et al 2015) or on the context of the action (Amoruso and Urgesi 2016), observation of an action pattern that disconfirmed their expectations suppressed motor resonance.…”
Section: The Muscle-specific Cse Decrease Mirrors Kinematic Adaptationssupporting
confidence: 60%
“…Conversely, in our deceived action condition, abrupt kinematics alterations occurred once the actors lifted an object of unexpected weight, but these alterations were aimed at successfully adapting the movement to the actual object weight. Thus, in our case and in all those studies (Senot et al 2011;Tomeo et al 2013;Mattiassi et al 2014;Janssen et al 2015) showing suppression of motor facilitation for unpredicted actions, the expected motor representation was incorrect and the observers had to rely on the incoming kinematic adaptations to understand the actual action outcome. In sum, we propose that the muscle-specific CSE decrease during observation of deceived actions might be due to the discrepancy between the kinematics pattern erroneously predicted on the basis of the reaching and grasping phases and the kinematic pattern correctly predicted on the basis of the observed adaptations during the lifting phase.…”
Section: The Muscle-specific Cse Decrease Mirrors Kinematic Adaptationsmentioning
confidence: 48%
“…The results showed that, even if the action viewed in peripheral vision—and then covertly attended—was effective in modulating the excitability of motor pathways, the accuracy of the motor response was low and rough. Along this line, other researchers adopted subliminal presentation of implied action images, demonstrating that the perceptual awareness of the action stimuli is required for motor resonance to occur ([36]; see also [37] for a behavioral demonstration). Schuch and colleagues [30] in an EEG study investigated the mu rhythm (oscillatory activity over sensorimotor cortex) and reported stronger activations of the motor system—as revealed by mu rhythm suppression—when an observed grasping action was relevant to the observers’ task (i.e., when they were later judging the grasp than when judging a colour change).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, studies using behavioural (Tausche et al, 2010;Orgs et al, 2011;Springer et al, 2011;Mattiassi et al, 2014) and neuroimaging methods (Ramnani & Miall, 2004;Stadler et al, 2011Stadler et al, , 2012Cross et al, 2013;Jacquet & Avenanti, 2015;Valchev et al, 2015) have demonstrated that the human AON is also sensitive to occluded actions. Indeed Ramnani & Miall (2004) found that merely informing participants that another person was acting via the presentation of an abstract symbol was sufficient to activate the AON.…”
Section: Introductionmentioning
confidence: 99%